2015
DOI: 10.1007/s00705-015-2593-x
|View full text |Cite
|
Sign up to set email alerts
|

Full genome sequences of torque teno sus virus strains that coinfected a pig with postweaning multisystemic wasting syndrome in Japan: implications for genetic diversity

Abstract: We determined the complete genome sequences of torque teno sus viruses (TTSuVs) detected in pigs with postweaning multisystemic wasting syndrome (PMWS) and in healthy pigs in Japan. Unexpectedly, we found coinfection of a PMWS-affected pig in Japan with one strain of TTSuV1, five strains of TTSuV2, and one strain of PCV2. Full-genome sequencing of each of these strains, followed by phylogenetic analysis, revealed broad genetic diversity in the TTSuV2 strains infecting the PMWS-affected pig. These results sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…However, these primers failed to detect TTSuV1 in our samples. In contrast, TTSuV1 was successfully detected in our samples using the primer pair reported by Ozawa et al [18]. A comparison of the primer sequences revealed that the reverse primer used by Ozawa et al [18] though almost identical to that of Kekarainen [19] differs by three NT bases at the 3' end.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…However, these primers failed to detect TTSuV1 in our samples. In contrast, TTSuV1 was successfully detected in our samples using the primer pair reported by Ozawa et al [18]. A comparison of the primer sequences revealed that the reverse primer used by Ozawa et al [18] though almost identical to that of Kekarainen [19] differs by three NT bases at the 3' end.…”
Section: Discussionmentioning
confidence: 58%
“…A comparison of the primer sequences revealed that the reverse primer used by Ozawa et al . [18] though almost identical to that of Kekarainen [19] differs by three NT bases at the 3’ end. The difference in the NT composition of Indian TTSuV1 in these positions could be the reason for the failure in our earlier attempts.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations